FBQS
Page-6.36Question 1:
7 – 9x + 2x2 is called a _________ polynomial.
Answer 1:
Polynomial with degree 2 is known as a quadratic polynomial.
Hence, 7 – 9x + 2x2 is called a quadratic polynomial.
Hence, 7 – 9x + 2x2 is called a quadratic polynomial.
Question 2:
12x – 7x2 + 4 – 2x3 is called a ___________ polynomial.
Answer 2:
Polynomial with degree 3 is known as a cubic polynomial.
Hence, 12x – 7x2 + 4 – 2x3 is called a cubic polynomial.
Hence, 12x – 7x2 + 4 – 2x3 is called a cubic polynomial.
Question 3:
13x2 – 88x3 + 9x4 is called a _________ polynomial.
Answer 3:
Polynomial with degree 4 is known as a biquadratic polynomial.
Hence, 12x – 7x2 + 4 – 2x3 is called a biquadratic polynomial.
Hence, 12x – 7x2 + 4 – 2x3 is called a biquadratic polynomial.
Question 4:
If x + 1 is a factor of the polynomial ax3 + x2 – 2x + 4a – 9, then a = __________.
Answer 4:
Let f(x) = ax3 + x2 – 2x + 4a – 9
It is given that one factor of f(x) is (x + 1).
Therefore, .
On putting x = –1 in f(x) = 0, we get
Hence, if x + 1 is a factor of the polynomial ax3 + x2 – 2x + 4a – 9, then a = 2.
It is given that one factor of f(x) is (x + 1).
Therefore, .
On putting x = –1 in f(x) = 0, we get
Hence, if x + 1 is a factor of the polynomial ax3 + x2 – 2x + 4a – 9, then a = 2.
Question 5:
If 3x – 1 is a factor of the polynomial 81x3 – 45x2 +3a – 6, then the value of a is ___________.
Answer 5:
Let f(x) = 81x3 – 45x2 +3a – 6
It is given that one factor of f(x) is (3x – 1).
Therefore, .
On putting x = in f(x) = 0, we get
Hence, if 3x – 1 is a factor of the polynomial 81x3 – 45x2 +3a – 6, then the value of a is
It is given that one factor of f(x) is (3x – 1).
Therefore, .
On putting x = in f(x) = 0, we get
Hence, if 3x – 1 is a factor of the polynomial 81x3 – 45x2 +3a – 6, then the value of a is
Question 6:
The remainders obtained when x3 + x2 – 9x – 9 is divided by x, x + 1 and x + 2 respectively are _________.
Answer 6:
Let f(x) = x3 + x2 – 9x – 9
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x,
we use remainder theorem, put x = 0.
f(0) is the remainder.
Now,
f(0) = (0)3 + (0)2 – 9(0) – 9
= –9
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x is –9.
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 1,
put x +1 = 0.
f(–1) is the remainder.
Now,
f(–1) = (–1)3 + (–1)2 – 9(–1) – 9
= –1 + 1 + 9 – 9
= 0
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 1 is 0.
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 2,
put x +2 = 0.
f(–2) is the remainder.
Now,
f(–2) = (–2)3 + (–2)2 – 9(–2) – 9
= –8 + 4 + 18 – 9
= 5
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 2 is 5.
Hence, the remainders obtained when x3 + x2 – 9x – 9 is divided by x, x + 1 and x + 2 respectively are –9, 0 and 5.
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x,
we use remainder theorem, put x = 0.
f(0) is the remainder.
Now,
f(0) = (0)3 + (0)2 – 9(0) – 9
= –9
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x is –9.
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 1,
put x +1 = 0.
f(–1) is the remainder.
Now,
f(–1) = (–1)3 + (–1)2 – 9(–1) – 9
= –1 + 1 + 9 – 9
= 0
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 1 is 0.
To find the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 2,
put x +2 = 0.
f(–2) is the remainder.
Now,
f(–2) = (–2)3 + (–2)2 – 9(–2) – 9
= –8 + 4 + 18 – 9
= 5
Hence, the remainder obtained when x3 + x2 – 9x – 9 is divided by x + 2 is 5.
Hence, the remainders obtained when x3 + x2 – 9x – 9 is divided by x, x + 1 and x + 2 respectively are –9, 0 and 5.
Question 7:
The remainder when f(x) = 4x3 – 3x2 + 2x – 1 is divided by 2x + 1 is __________.
Answer 7:
Let f(x) = 4x3 – 3x2 + 2x – 1
To find the remainder obtained when 4x3 – 3x2 + 2x – 1 is divided by 2x + 1,
we use remainder theorem, put 2x + 1 = 0.
f() is the remainder.
Now,
Hence, the remainder when f(x) = 4x3 – 3x2 + 2x – 1 is divided by 2x + 1 is
To find the remainder obtained when 4x3 – 3x2 + 2x – 1 is divided by 2x + 1,
we use remainder theorem, put 2x + 1 = 0.
f() is the remainder.
Now,
Hence, the remainder when f(x) = 4x3 – 3x2 + 2x – 1 is divided by 2x + 1 is
Question 8:
The degree of a polynomial f(x) is 7 and that of polynomial f(x) g(x) is 56, then degree of g(x) is ________.
Answer 8:
Given:
Degree of a polynomial f(x) = 7
Degree of polynomial f(x) g(x) = 56
Degree of polynomial f(x) g(x) = Degree of polynomial f(x) × Degree of polynomial g(x)
⇒ 56 = 7 × Degree of polynomial g(x)
⇒ Degree of polynomial g(x) =
⇒ Degree of polynomial g(x) = 8
Hence, degree of g(x) is 8.
Degree of a polynomial f(x) = 7
Degree of polynomial f(x) g(x) = 56
Degree of polynomial f(x) g(x) = Degree of polynomial f(x) × Degree of polynomial g(x)
⇒ 56 = 7 × Degree of polynomial g(x)
⇒ Degree of polynomial g(x) =
⇒ Degree of polynomial g(x) = 8
Hence, degree of g(x) is 8.
Question 9:
The remainder when x15 is divided by x + 1 is __________.
Answer 9:
Let f(x) = x15
To find the remainder obtained when x15 is divided by x + 1,
we use remainder theorem, put x + 1 = 0.
f(−1) is the remainder.
Now,
Hence, the remainder when x15 is divided by x + 1 is −1.
To find the remainder obtained when x15 is divided by x + 1,
we use remainder theorem, put x + 1 = 0.
f(−1) is the remainder.
Now,
Hence, the remainder when x15 is divided by x + 1 is −1.
Question 10:
If
Answer 10:
Let p(x) = x2 – 4x + 3
Hence, if
Hence, if
Question 11:
If the polynomial f(x) = 5x5 – 3x3 + 2x2 – k gives remainder 1 when divided by x + 1, then k = __________.
Answer 11:
Let f(x) = 5x5 – 3x3 + 2x2 – k
To find the remainder obtained when 5x5 – 3x3 + 2x2 – k is divided by x + 1,
we use remainder theorem, put x + 1 = 0.
f(−1) is the remainder.
Now,
Hence, k = –1.
To find the remainder obtained when 5x5 – 3x3 + 2x2 – k is divided by x + 1,
we use remainder theorem, put x + 1 = 0.
f(−1) is the remainder.
Now,
Hence, k = –1.
Question 12:
The remainder when f(x) = x45 is divided by x2 – 1 is ____________.
Answer 12:
Let f(x) = x45
To find the remainder obtained when x45 is divided by x2 – 1,
Let the remainder (r) be ax + b.
Then,
f(x) = (x2 – 1) q + r
Therefore, the remainder (r) = 1(x) + 0 = x.
Hence, the remainder when f(x) = x45 is divided by x2 – 1 is x.
To find the remainder obtained when x45 is divided by x2 – 1,
Let the remainder (r) be ax + b.
Then,
f(x) = (x2 – 1) q + r
Therefore, the remainder (r) = 1(x) + 0 = x.
Hence, the remainder when f(x) = x45 is divided by x2 – 1 is x.
No comments:
Post a Comment